ChemInform Abstract: Air‐Stable Palladium(0) Phosphine Sulfide Catalysts for Ullmann‐Type C—N and C—O Coupling Reactions. Issue 27 (18th June 2015) - Majumder, Arpi; Gupta, Ragini; Mandal, Mrinmay; Babu, Madhu; Chakraborty, Debashis
Abstract Phenyl bromide as reaction partner in amination and etherification gives similar (amination) or lower (etherification) yields at longer reaction times.